The Effectiveness of Augmented Reality–Based Islamic Education Learning on Students’ Learning Motivation at SMA Al Fatih Simpang Rimba, Kepulauan Bangka Belitung - Dian Rezki Pratama; Sumarli Sumarli (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective– This study aims to examine the effectiveness of Augmented Reality (AR)–based Islamic education learning in enhancing students’ learning motivation at SMA Al Fatih Simpang Rimba, Kepulauan Bangka Belitung, addressing the limited empirical evidence on motivational outcomes of AR integration in non-formal educational settings. Methodology– A quantitative quasi-experimental method employing a pretest–posttest non-equivalent control group design was applied. The sample consisted of 38 students divided into an experimental group receiving AR-based instruction and a control group receiving conventional learning. Students’ learning motivation was measured using a validated ARCS-based questionnaire. Data were analyzed using descriptive statistics, assumption testing Findings– The results indicate a statistically significant improvement in learning motivation among students exposed to AR-based Islamic education learning. The experimental group demonstrated substantially higher posttest motivation scores than the control group. Dimension-level analysis revealed strong effects on attention and relevance, with moderate yet significant effects on confidence and satisfaction. Research Implications/Limitations–  The findings suggest that AR-based learning can effectively enhance motivational engagement in Islamic education, particularly within senior high school contexts. However, the study is limited by its short intervention duration and focus on motivational variables. Originality/Value–  This study contributes novel insights by focusing on learning motivation as the primary outcome and situating AR-based Islamic education learning within a senior high school environment, thereby enriching both motivational theory and digital Islamic pedagogy.